2019
DOI: 10.1128/jvi.01783-18
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of CH31 Broadly Neutralizing Antibody Does Not Affect Development of Vaccine-Induced Anti-HIV-1 Envelope Antibody Responses in Infant Rhesus Macaques

Abstract: Prevention of mother-to-child transmission (MTCT) is an indispensable component in combatting the global AIDS epidemic. A combination of passive broadly neutralizing antibody (bnAb) infusion and active vaccination promises to provide protection of infants against MTCT from birth through the breastfeeding period and could prime the immune system for lifelong immunity. In this study, we investigate the impact of a single infusion of CD4 binding site (CD4bs) bnAb administered at birth on de novo antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(71 citation statements)
references
References 34 publications
9
62
0
Order By: Relevance
“…Consistent with the data from early human pediatric vaccine trials (10), we also observed persistence of Env-specific antibody responses after vaccination in early life (12). In addition, we recently reported that passive administration of an HIV Env-specific broadly neutralizing monoclonal antibody at birth does not interfere with the induction of Env-specific antibody responses by vaccination in infant macaques (15).…”
Section: Importancesupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the data from early human pediatric vaccine trials (10), we also observed persistence of Env-specific antibody responses after vaccination in early life (12). In addition, we recently reported that passive administration of an HIV Env-specific broadly neutralizing monoclonal antibody at birth does not interfere with the induction of Env-specific antibody responses by vaccination in infant macaques (15).…”
Section: Importancesupporting
confidence: 90%
“…CH31 was administered to provide passive immunity during the time antibody responses were developing in response to vaccination. The vaccine-induced antibody responses up to week 14, 2 weeks after the 3rd boost, were previously reported (15). The goal of the earlier study was to document that passive administration of a bNAb at the time of the vaccine prime does not interfere with the induction of vaccine-induced antibody responses in infants.…”
Section: Summary Of Vaccine-induced Antibody Responses After 3 Immunimentioning
confidence: 82%
“…Type D retrovirus-, SIV- and STLV-1 free Indian rhesus macaques (RM) ( Macaca mulatta ) were maintained in the colony of California National Primate Research Center (CNPRC, Davis, CA), as previously described (47). Six infant RMs were orally challenged with SHIV.CH505.375H.dCT (22) as described in (26).…”
Section: Methodsmentioning
confidence: 99%
“…The positivity cut off for the assay was defined as the optical density (OD) of the lowest-concentration rhesus IgG standard that was greater than three times the average OD of blank wells. CD4 blocking ELISAs were done as described in (47).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation